Analisis Pola Komunikasi Interpersonal Guru dengan Siswa dalam Membentuk Kemandirian Siswa Tunagrahita di Sekolah Luar Biasa (SLB C Karya Tulus) - Hsb, Saima Putri; Yusniah; Mantondang, Muhammad Alfikri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Learning to be independent presents a number of challenges for students with intellectual disabilities, including communication and social interaction issues. Their capacity to comprehend directions, communicate needs, and interact with people may be impacted by this. In addition, individuals with intellectual disabilities often struggle with emotional regulation, which makes it more difficult for them to adjust to their environment. This highlights the necessity of offering suitable help and guidance in the field of education so that individuals with intellectual disabilities can reach their full potential. It turns out that the development of independence in students with intellectual disabilities is significantly influenced by the quality of interpersonal connection between teachers and students. Using a case study at a Special School (SLB C Karya Tulus), this study intends to examine interpersonal communication patterns between instructors and students in the context of helping individuals with intellectual disabilities become more independent. The descriptive approach, combined with a qualitative research methodology, aims to provide verbal interpretations of the research findings. Direct observation, teacher and administrator interviews, and the review of pertinent documents were the methods used to gather data. The study's findings demonstrate the critical role that interpersonal communication has in the development of student independence between mentally handicapped pupils at SLB C Karya Tulus and their teachers. Good and honest communication can boost students' enthusiasm to learn, give them more self-assurance, and improve the bond between teachers and students. These results highlight how crucial it is to focus on the interpersonal communication quality in order to assist students with intellectual disabilities in developing their independence in an inclusive learning environment.